Kritik Comic dalam Kompetisi Kritik DPR 2018 sebagai Praktik Demokrasi - Ananda Ashari; Adi Bayu Mahadian (Jurnal Komunikasi)
Stand-up comedy can function as a medium of entertainment as well as a media channeling people's aspirations including political criticism as a form of democracy. This research uses Teun A. van Dijk's discourse analysis method which is supported by bisociation theory as one of humor theories, with the aim of the research to find out the theme, discourse, humorous discourse display and the role of stand-up comedy as a form of democracy based on Aji Pratama's stand-up comedy in 2018 DPR critics competition. The results of this study explain that the theme raised in the Aji Pratama material is the bad behavior of the DPR with humorous discourse in the form of humor, which is mostly presented in the form of negotiations and conveyed subtly through elements of van Dijk. The phenomenon is an illustration of the form of democracy in Indonesia which is at the same time a contribution of this research to the study of democracy. This research also contributes to the study of humor theory through the use of bisociation theory to show how even critical discourse can be packaged in the form of humor.